Comparative Study on Wood CNC Routing Methods for Transposing a Traditional Motif from Romanian Textile Heritage into Furniture Decoration - Lungu Antonela; Ispas Mihai; Brenci Luminita Maria; Racasan Sergiu; Cosereanu Camelia (Applied Sciences-Basel, 2021)
This paper presents experimental research on the Computer Numerical Control (CNC) routing of a traditional motif collected from ¸Tara Bârsei (Transylvania region) using two methods, namely, engraving (Engrave) and carving (V-Carve). The analysis of the CNC router processes includes the calculation of the path lengths, an assessment of the processing time and wood mass loss, and an evaluation of the tool wearing by investigating the tool cutting edge on a Stereo Microscope NIKON SMZ 18 before and after processing the ornament on wood. An aesthetic evaluation of the ornament routed on wood, using both the engraving and carving methods, is also conducted, whilst a microscopic analysis of the processed areas highlights the defects that occurred on the wood surface depending on the tool path.
Keywords: CNC router; textile heritage; stereo-microscopy investigation; traditional motif